Mutiara Mahkota Launched - Siti Sarah, Mohamad Rajimi (2017)
Kuantan - Universiti Malaysia Pahang (UMP) launched a book named Mutiara Mahkota: Tengku Abdullah al-Haj in conjunction with Universiti Malaysia Pahang (UMP) 12th Convocation Ceremony.